Assessment of Knowledge of Risk Factors of Breast Cancer among Nurses in Services Hospital Lahore - Jamil, Nabila; Parveen, Rashida; Ambreen, Saba; Ashiq, Sofia; Anwar, Saima (Indus Journal of Bioscience Research, 2025)
Background: Breast cancer is one of the most prevalent cancers worldwide and a leading cause of cancer-related mortality among women. Nurses play a critical role in educating patients about breast cancer, its risk factors, and the importance of early screening. Objective: The aim of this study is to assess the knowledge of nurses of Service Hospital Lahore about the Risk Factors of Breast Cancer. Methodology: This cross-sectional study was conducted among 133 nurses at Services Hospital Lahore from November 2024 to December 2024. A structured questionnaire was used to collect data on demographics and knowledge of risk factors. Results: showed a diverse demographic profile, with a majority of female nurses aged 20-35 years. Nurses’ knowledge varied significantly. While 60.1% correctly identified painless breast lumps as a sign of cancer, and over 50% recognized stress and late menopause as risk factors, knowledge was lower for lifestyle factors like smoking (47.3%), alcohol (42.1%), and obesity (41.3%). Notably, only 14.2% of the nurses demonstrated good knowledge, 57.1% had average knowledge, and 28.5% exhibited poor knowledge. This highlights significant knowledge gaps, particularly regarding hormonal and lifestyle-related risk factors. Conclusion: The study concludes that targeted educational interventions are crucial to enhance nurses’ understanding of breast cancer risk factors, thereby improving patient education and early detection efforts. Further research is recommended to explore factors influencing nurses’ knowledge and to develop effective, tailored interventions.